2010
DOI: 10.1089/jwh.2009.1759
|View full text |Cite
|
Sign up to set email alerts
|

Comparing an Olive Oil-Enriched Diet to a Standard Lower-Fat Diet for Weight Loss in Breast Cancer Survivors: A Pilot Study

Abstract: An olive oil-enriched diet brought about greater weight loss than a lower-fat diet in an 8-week comparison. Moreover, these women chose, overwhelmingly, the olive oil-enriched diet for 6 months of follow-up. An olive oil-enriched diet may be more efficacious for weight loss in breast cancer survivors than a standard lower-fat diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 44 publications
(42 reference statements)
1
23
0
Order By: Relevance
“…This anomaly was also seen in previous com- parisons of the olive oil diet to lower fat diets [11] [21]. Despite the similar weight loss and higher energy intake, the diet that included extra virgin olive oil resulted in lower levels of fasting glucose, insulin and HOMA.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This anomaly was also seen in previous com- parisons of the olive oil diet to lower fat diets [11] [21]. Despite the similar weight loss and higher energy intake, the diet that included extra virgin olive oil resulted in lower levels of fasting glucose, insulin and HOMA.…”
Section: Discussionsupporting
confidence: 58%
“…This protocol was based on an earlier pilot study by the PI that compared the National Cancer Institute diet for women with breast cancer to the same plant-based, olive oil diet [11]. In that study, however, weight loss was greater on the olive oil diet compared to the lower fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women previously diagnosed with invasive breast cancer, an OO supplement of 3 tablespoons of OO/day for 8 weeks resulted in higher HDL-C in comparison with the National Cancer Institute diet [123].…”
Section: Cancermentioning
confidence: 85%
“…us, it was revealed that an olive oil-enriched diet may be more efficacious for weight loss in breast cancer survivors than a standard lower-fat diet [16]. Until the early 1960s, the traditional recipe "Arkouy" from the mixture of carob (Ceratonia siliqua L.) powder and olive (Olea europaea L.) oil represented a sought-after food product in some localities of this region.…”
Section: Introductionmentioning
confidence: 99%